1998
DOI: 10.1109/32.708566
|View full text |Cite
|
Sign up to set email alerts
|

Model checking large software specifications

Abstract: Abstract-In this paper, we present our experiences in using symbolic model checking to analyze a specification of a software system for aircraft collision avoidance. Symbolic model checking has been highly successful when applied to hardware systems. We are interested in whether model checking can be effectively applied to large software specifications. To investigate this, we translated a portion of the state-based system requirements specification of Traffic Alert and Collision Avoidance System II (TCAS II) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
139
2
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 203 publications
(143 citation statements)
references
References 46 publications
0
139
2
2
Order By: Relevance
“…All our TCAS II experiments were performed on a Sun Sparc 10 with 128MB of main memory, while other data were collected on a Sun Ultra 2 with 256 MB of main memory. Note that the TCAS II model analyzed was slightly different from the one examined in the initial study [3], so the data reported there should not be directly compared with the results in this paper.…”
Section: State-set Optimizationsmentioning
confidence: 51%
See 4 more Smart Citations
“…All our TCAS II experiments were performed on a Sun Sparc 10 with 128MB of main memory, while other data were collected on a Sun Ultra 2 with 256 MB of main memory. Note that the TCAS II model analyzed was slightly different from the one examined in the initial study [3], so the data reported there should not be directly compared with the results in this paper.…”
Section: State-set Optimizationsmentioning
confidence: 51%
“…Its application to nontrivial software or process-control systems is far less mature, but is increasingly promising. For example, we obtained encouraging results from applying symbolic model checking to a portion of a preliminary version of the system requirements specification of TCAS II, a complex system for mid-air collision avoidance [3]. The full requirements, comprising about 400 pages, are written in the Requirements State Machine Language (RSML) [4], a state-machine language based on statecharts [5].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations